Rhetoric and Reality: Augustine and Pope Francis on Preaching Christ and the Poor. (September 2019) - Grove, Kevin
In an age when rhetoric about alleviating conditions of poverty is rightly suspect, this study offers a reassessment of the power of non-modern, christological rhetoric through parallel examples of the preaching of Augustine and Pope Francis. Demonstrating how both practice a version of prosopopeia, this study shows how Augustine's "exchange" and Francis's "encounter" function as performative Christologies by which rhetoric is meant to effect reality concerning the poor. The study suggests revision of binary formulations of the relation of rhetoric to reality and proposes a non-binary, incarnational method.